Pro Spring Boot 2 : an authoritative guide to building microservices, web and enterprise applications, and best practices - Gutierrez, Felipe (Albuquerque, NM, USA : Apress, 2019)
Quickly and productively develop complex Spring applications and microservices - out of the box - with minimal fuss on things like configurations. This book will show you how to fully leverage the Spring Boot productivity suite of tools and how to apply them through the use of case studies. Pro Spring Boot is your authoritative hands-on practical guide for increasing your Spring Framework-based enterprise Java and cloud application productivity while decreasing development time using the Spring Boot productivity suite of tools. It's a no nonsense guide with case studies of increasing complexity throughout the book. This book is written by Felipe Gutierrez, a Spring expert consultant who works with Pivotal, the company behind the popular Spring Framework. What You Will Learn Write your first Spring Boot application Configure Spring Boot Use the Spring Boot Actuator Carry out web development with Spring Boot Build microservices with Spring Boot Handle databases and messaging with Spring Boot Test and deploy with Spring Boot Extend Spring Boot and its available plug-ins Who This Book Is For Experienced Spring and Java developers seeking increased productivity gains and decreased complexity and development time in their applications and software services.
1. Introduction to Spring Boot -- 2. Your First Spring Boot application -- 3. Spring Boot Configuration -- 4. Introduction to Spring Boot Actuator -- 5. Spring Boot CLI -- 6. Web Development with Spring Boot -- 7. Databases and Data Access with Spring Boot -- 8. Building Microservices with Spring Boot -- 9. Messaging with Spring Boot -- 10. Testing with Spring Boot -- 11. Deploying Spring Boot -- 12. More on Spring Boot Actuator -- 13. Extending Spring Boot -- 14. Maven and Gradle Plug-ins -- 15. Other Spring Boot Plug-ins.
Includes index.
Book Finder International
Keywords: Computer science; Java (Computer program language).; Java; Computer Science, general